A fuzzy-rule-based PV inverter controller to enhance the quality of solar power supply: Experimental test and validation - Hannan M.A.; Ghani Z.A.; Hoque M.M.; Hossain Lipu M.S. (MDPI AG, 2023)
This paper presents the development of fuzzy-based inverter controller for photovoltaic (PV) application to avoid the nonlinearity characteristic and fluctuations of PV inverter output. The fuzzy-based controller algorithm is employed in the PV inverter control system to optimize the duty cycles of the insulated-gate bipolar transistors (IGBTs) and to enhance the inverter outputs with lower harmonic contents and unity power factor. The developed fuzzy-based PV inverter controller is implemented in the MATLAB/Simulink models and experimentally tested in a dSPACE DS1104 process controller. The obtained simulation result of the developed fuzzy-based PV inverter controller is validated with experimental results under different performance conditions. It is seen that the experimental results of the switching signals, inverter voltage and current, control parameters, and total harmonic distortion (THD) of load current and output voltage of the PV inverter are closely matched with that of the simulation results. To validate the inverter performance, the proposed fuzzy-based PV inverter controller outperforms other studies with a voltage THD of 2.5% and a current THD of 3.5% with unity power factor. 2019 by the authors. Licensee MDPI, Basel, Switzerland.